Alternative Splicing of the Lobster (Homarus americanus) Crustacean Hyperglycemic Hormone A and B Genes Produce 2 Protein Variants Involved in Vitellogenin Inhibition - Wang, Cheng Gui; Wang, Wei; Shi, Li Li; Shen, Yu Chun; Chan, Siuming F. (Frontiers in Marine Science, 2022)
Current BLASTP search analysis results suggested that the lobster (Homarus americanus) HaCHH-A and HaCHH-B may be derived from 2 different 4-exon genes and repeated tissues expression studies have revealed a much different expression pattern of these two genes as it was reported in the past. By RT-PCR, RACE cDNA and genomic DNA cloning, we confirmed that the HaCHH-A and HaCHH-B transcripts are derived from two different 4-exon CHH genes. By alternative splicing mechanism, each gene can produce different but larger transcript variants (i.e. sHaCHH-A and sHaCHH-B) mainly in different non-eyestalk tissues of the females. The larger and unspliced transcripts can be detected in the hepatopancreas, gill, heart, nerve cord, brain, ovary and thoracic ganglion of the reproductive females. The expression pattern of sHaCHH-A and sHaCHH-B in other non-eyestak tissues suggests that these transcripts have a wide spectrum of expressions during the female reproductive cycle. An in vitro organ explant culture system was developed to investigate the reproductive function of these cDNAs. Results showed that recombinant protein for sHaCHH-A and sHaCHH-B inhibited vitellogenin gene expression whereas dsRNA for sHaCHH-A and sHaCHH-B inhibited the expression of vitellogenin gene in vitro. The results of the study may provided insight for the development of technique to induce gonad development without the use of the eyestalk ablation operation. This is the first in-depth report for the characterization of two 4-exon CHH genes in a crustacean.